Forensic analysis of mixed semen and vaginal fluids via ATR-FTIR spectroscopy for identification purposes in sexual aggression cases - Tuğba Ünsal Sapan; İrem Hersekli (Bulletin of the National Research Centre)
Abstract Background Forensic science is an interdisciplinary field that applies principles and techniques from the natural and physical sciences to matters of law and criminal justice. As an academic discipline, forensic science encompasses a broad range of scientific methods used to analyze physical evidence from crime scenes to aid in investigations, legal proceedings, and the enforcement of justice. Within this field, forensic genetics plays a pivotal role by employing genetic material obtained from biological samples at crime scenes to establish associations between suspects and criminal acts, particularly in cases involving sexual assault. Furthermore, the accurate identification of biological fluids is integral to the advancement of forensic investigations. In the context of sexual offenses, spectroscopic techniques have gained prominence for their capacity to analyze body fluids (such as semen and vaginal fluid) on substrates taken from the victims’ body or at the scene rapidly and non-destructively, without sample destruction or the need for extensive sample preparation. Among these techniques, Fourier Transform Infrared (FTIR) spectroscopy stands out due to its ability to provide rapid, cost-effective, and non-invasive analysis while preserving the integrity and quantity of the biological specimen. Results The present study investigates the application of FTIR spectroscopy for the identification of seminal fluid, vaginal fluid, and their combinations on two fabric substrates: white cotton and patterned nylon. Spectral analysis enabled the identification of distinct functional groups associated with each type of biological fluid. Spectral markers specific to vaginal fluid and mixed samples were successfully distinguished. Conclusion A notable finding of the study was the identification of the PSA/Fructose functional group as a biochemical marker indicative of seminal fluid within mixed samples containing vaginal secretions. Although both seminal and vaginal fluids were found to share five common biomolecular components, the presence of a distinct PSA/Fructose peak was characteristic of seminal fluid, whereas the detection of a glycogen peak—attributed to epithelial shedding from the cervix—was indicative of vaginal fluid. This distinction facilitated the clear differentiation between seminal and vaginal constituents within mixed biological samples. These results highlight the efficacy and reliability of Fourier Transform Infrared (FTIR) spectroscopy as a forensic tool for the identification of biological fluids, particularly in the context of sexual assault investigations.